2021
DOI: 10.1159/000513621
|View full text |Cite
|
Sign up to set email alerts
|

Medium Cut-Off Dialysis Membranes: Can They Have Impact on Outcome of COVID-19 Hemodialysis Patients?

Abstract: <b><i>Introduction:</i></b> Severe acute respiratory syndrome coronavirus-2 may lead to high levels of expression of inflammatory cytokines. Medium cut-off (MCO) membranes may make greater clearances for large-middle molecules (including cytokines) than low-flux (LF) membranes. In this study, we aimed to evaluate the impact of MCO membranes on outcome of COVID-19 patients on hemodialysis (HD). <b><i>Methods:</i></b> Sixty COVID-19 HD patients were included in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…However, this study was focused on inflammatory mediator changes: pre-and post-HD IL-6 blood levels were measured only in the first session (HD with MCO) at diagnosis and no significant differences were detected [17]. Yalin et al [39] did not find any difference in mortality in a retrospective study that examined 60 CHD patients affected by SARS-CoV-2 treated with MCO or low-flux membranes. Tarakcioǧlu et al [40] evaluated cytokines removal in 21 stable CHD patients treated with low-flux HD and did not find any difference as to IL-1 beta, IL-6, TNF-alpha, and sIL-2R concentrations between pre-and post-HD specimens.…”
Section: Discussion/conclusionmentioning
confidence: 98%
“…However, this study was focused on inflammatory mediator changes: pre-and post-HD IL-6 blood levels were measured only in the first session (HD with MCO) at diagnosis and no significant differences were detected [17]. Yalin et al [39] did not find any difference in mortality in a retrospective study that examined 60 CHD patients affected by SARS-CoV-2 treated with MCO or low-flux membranes. Tarakcioǧlu et al [40] evaluated cytokines removal in 21 stable CHD patients treated with low-flux HD and did not find any difference as to IL-1 beta, IL-6, TNF-alpha, and sIL-2R concentrations between pre-and post-HD specimens.…”
Section: Discussion/conclusionmentioning
confidence: 98%
“…Medium cut-off membranes are quite promising and their benefits in COVID-19 patients have been reported before. 12 , 13 COVID severity was the most important factor for mortality in our multivariate model whereas inflammatory markers and co-morbidities were not found to be significant. This might be because, high levels of inflammatory markers are related to COVID severity and hemodialysis patients already have a high burden of co-morbidities.…”
Section: Discussionmentioning
confidence: 55%
“…A study by Esposito et al [15] compared the MCO dialyzer with a protein-leaking membrane dialyzer in 29 HD patients with COVID-19 and found that IL-6 RR was 10% with MCO, which is similar to the IL-6 RR seen in our study. Yalin et al [14] have reported data from 60 COVID-19 HD patients from a hospital that uses LF dialyzer and from another hospital that uses the MCO dialyzer and show that mortality was 16.6% (4/24 patients) in the MCO group and 26.4% (10/36 patients) in the LF group. Death and need for ICU were similar in both hospitals, even though MCO dialyzer patients had higher ferritin and CRP.…”
Section: Discussionmentioning
confidence: 99%
“…The new dialyzer membrane, namely, the medium cut-off (MCO) membrane, can remove large middle molecules and inflammatory cytokines in chronic HD patients [9][10][11][12][13], and both dialysis and cytokine removal can be simultaneously performed in the same session. However, as very few studies have evaluated the effects of dialyzer membrane types in chronic HD patients with COVID-19, the results remain inconclusive [14,15]. Hence, this study aimed to compare MCO and low-flux (LF) membrane dialyzers in terms of IL-6 reduction, change in inflammatory state, intradialytic complications, and mortality in chronic HD patients diagnosed with COVID-19.…”
Section: Introductionmentioning
confidence: 99%